In Vitro Virucidal and Virustatic Properties of the Crude Extract of Cynodon dactylon against Porcine Reproductive and Respiratory Syndrome Virus - Kidsadagon Pringproa; Oapkun Khonghiran; Suchaya Kunanoppadol; Teerapong Potha; Phongsakorn Chuammitri (Veterinary Medicine International)
The in vitro virustatic and virucidal tests of the crude extract of Cynodon dactylon against infection with porcine reproductive and respiratory syndrome virus (PRRSV), a cause of major devastating pig disease, were described. Crude extract of C. dactylon was prepared for cytotoxicity on tissue-culture cells that were used to measure virustatic and virucidal activities against PRRSV. Crude extract of C. dactylon at 0.78 mg/mL showed no cytotoxicity on the cell line, and at that concentration significantly inhibited replication of PRRSV as early as 24 hours post infection (hpi). C. dactylon also inactivated PRRSV as determined by immunoperoxidase monolayer assay (IPMA) compared to the control experiments. In summary, the present study may be among the earliest studies to describe virustatic and virucidal activities of C. dactylon crude extract against PRRSV in vitro. Extracts of C. dactylon may be useful for PRRSV control and prevention on pig farms.